Using Creativity Approach in Mining: Integrating OTSM-TRIZ and AHP by assessing resource maturity level for new Solutions - Nikulin, Christopher; Valdes, Cristian; Piñones, Eduardo; Viveros, Pablo (LACCEI, 2024)
Mining problems are increasingly complex, involving technical, economic, and human variables due to ongoing process, machine, and technology improvements. Effective maintenance for this new generation remains a challenge. Innovative maintenance methods and tools are crucial for identifying failures and proposing solutions that align with companies' needs, ensuring feasible real-world implementation. This article introduces a method inspired by the Theory of Inventive Problem Solving (OTSM-TRIZ) and Resource Analysis to understand implementation risks. A step-by-step procedure structures the problem context through elicitation, classification, and evaluation. The Analytic Hierarchy Process (AHP) reinforces decision-making analysis. A case study demonstrates the method's application through four stages: i) forming working groups to gather information across company levels; ii) using a Network of Problems (NoP) to identify issues and potential solutions; iii) applying Resource Analysis to understand implementation challenges; and iv) employing AHP to compare NoP solutions and determine the most suitable one. This methodology fosters idea creation, addresses risks, and facilitates decision-making, leading to robust and effective mining project proposals